1926
DOI: 10.1037/h0070587
|View full text |Cite
|
Sign up to set email alerts
|

Sonance as a form of tonal fusion.

Abstract: Physics and psychophysics have always regarded fusion of pitches and their intensities as a simultaneous subjective phenomenon, dependent on the form of the molecular motion energizing the ear. This concept of tonal fusion has been built up in terms of a single sound wave. Timbre (tonequality, tone-color, or quality), has been defined as a simultaneous fusion of pitches, and has been considered as the unique variable quality of the clang, or single complex tone.* Ladd and Woodworth state that ". . . tone-color… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

1928
1928
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…The Analysis-by-Synthesis approach that this study is based on reaches back to Seashore and his colleagues, like Metfessel [17,15]. It was outlined in detail by Bengtsson and Gabrielsson [1].…”
Section: Methodsmentioning
confidence: 99%
“…The Analysis-by-Synthesis approach that this study is based on reaches back to Seashore and his colleagues, like Metfessel [17,15]. It was outlined in detail by Bengtsson and Gabrielsson [1].…”
Section: Methodsmentioning
confidence: 99%
“…Most importantly, the experiments of Milton Metfessel (1926) showed that listeners were unaware of the vibrato parameters. When not told what they were listening to, they rather reported a certain timbre.…”
Section: The Vibrato In Music Psychologymentioning
confidence: 99%
“…When told, they could not say whether pitch or loudness was manipulated. Since Metfessel (1926) wanted the term "timbre" to be reserved for the description of the multiple frequencies and their proportions within a static sound, he tried to introduce the term "sonance", which should describe the dynamic changes of the parameters constituting the vibrato, including rapid changes in fundamental frequency, amplitude and timbre. Unfortunately, the term "sonance" was never established, so today we are still facing similar terminological problems.…”
Section: The Vibrato In Music Psychologymentioning
confidence: 99%
“…This is a type of psychophysics which, in Seashore's (20) terminology, " measures the output." The only attempt so far made to apply the older type of psychophysical approach to the vibrato, i.e., to control the stimulus and determine what is heard, is that of Metfcssel (13,14). He showed that, in synthetic vibratos produced by means of siren discs, the quality of a tone is determined not only by its wave-form but also by the characteristics of its vibrato.…”
mentioning
confidence: 99%
“…and is exactly counterbalanced. This drum had been used by Metfessel (13,14) in some previous experiments. The discs were made of tough cardboard and were held on top of the drum by a counterbalanced cast-iron plate.…”
mentioning
confidence: 99%